Contribution to the knowledge of lycophytes and ferns of Españita, Tlaxcala, Mexico - Castañeda-Díaz, Saúl; Granados Victorino, ESPAÑOL; Sánchez-González, ESPAÑOL (Ecosistemas y Recursos Agropecuarios, 2023)
The non-existence of a complete list of lycophytes and ferns for the state of Tlaxcala motivated this work, whose objective is to document the richness of pteridoflora existing in Tlaxcala state. From 2013 to 2018, the collection of 34 numbers of lycophytes and ferns was carried out in the municipality of Españita, the plants were herbalized, identified and deposited in the Jorge Espinoza Salas (JES) Herbarium, the specimens corresponds to eight families, 15 genera and 23 taxa. Of these, two taxa are of the genus Selaginella P. Beauv. From the sources consulted, a list of 58 taxa was prepared for the state, which implies that 39.6% of the taxa known in the entity are found in the municipality of Españita. Of these, two are new records for the state: Marsilea mollis B.L. Rob. & Fernald and Polypodium guttatum Maxon. 20 taxa are terrestrial; two, epiphytes, and one, aquatic. The types of vegetation with more taxa are the forests of Quercus spp. and Juniperus deppeana Steud. Although the vegetation of the municipality of Españita is secondary vegetation, it is possible to find in it a considerable richness of species capable of being conserved.